2009
DOI: 10.1186/1746-4269-5-24
|View full text |Cite
|
Sign up to set email alerts
|

The Ethnomedicine of the Haya people of Bugabo ward, Kagera Region, north western Tanzania

Abstract: Background: The Kagera region, in north western Tanzania, is endowed with a strong culture of traditional medicine that is well supported by a rich diversity of medicinal plants. However, most of the plants in this region have not been documented nor evaluated for safety and efficacy. As an initiative in that direction, this study documented the knowledge on medicinal plant use by traditional healers of Bugabo Ward in Bukoba District.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 19 publications
5
53
1
Order By: Relevance
“…The analysis of the biological forms of healing plants used in the study area revealed that most of the species are shrubs (32 %), followed by herbs (21 %), trees (16 %), hemicryptophytes (12 %), subshrubs (11 %), and geophytes (8 %) ( Figure n°6). This result is against other studies in which trees were the shape of the most dominant growth (AddoFordjour et al, 2008;Moshi et al, 2009). In the study area, as in most regions of Morocco as well as in other countries, a conflict exists between plant use and resources preservation (Sheldon et al, 1998;Kala, 2000;Agelet & Vallés, 2001).…”
Section: Diversity Of Medicinal Plantscontrasting
confidence: 55%
“…The analysis of the biological forms of healing plants used in the study area revealed that most of the species are shrubs (32 %), followed by herbs (21 %), trees (16 %), hemicryptophytes (12 %), subshrubs (11 %), and geophytes (8 %) ( Figure n°6). This result is against other studies in which trees were the shape of the most dominant growth (AddoFordjour et al, 2008;Moshi et al, 2009). In the study area, as in most regions of Morocco as well as in other countries, a conflict exists between plant use and resources preservation (Sheldon et al, 1998;Kala, 2000;Agelet & Vallés, 2001).…”
Section: Diversity Of Medicinal Plantscontrasting
confidence: 55%
“…The plants used in this study are among plants recently reported as being used in traditional medicine in Bukoba rural district (Moshi et al, 2009). The material for this study was collected from Bukoba district in November, 2008 by Mr. Didas Ngemera, a traditional healer participating in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Two recent studies in Bukoba rural district (Kisangau et al, 2007;Moshi et al, 2009) have set the pace and more studies are ongoing. This study reports on brine shrimp toxicity tests of extracts from some of the plants reported from Bugabo Ward in Kagera region by Moshi et al (2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roots are chewed to combat indigestion. 4 As snake-bite antidote, to cleanse the uterus, in skin diseases 5 and increase milk production after child birth, 6 gonorrhea and haemorrhoids, as pesticides, 5 anti feedant in worms, anti-inflammatory, antifungal and antiviral, 7,8 antibacterial activity, diabetes, 9 rheumatism, migraine headache, management of epilepsy, cough and treatment of tuberculosis, 10 mosquito repellant against Anopheles arabiensis, syphilis, kidney ailments and against HIV. 11 A decoction prepared from boiled stem bark extract of C. anisata was taken internally for two weeks by akwaibom state people to treat measles.…”
Section: Introductionmentioning
confidence: 99%